Carcass characteristics of small and medium-frame Aberdeen Angus young steers - Miguelangelo Ziegler Arboitte (Acta Scientiarum. Animal Sciences, 2012)
Carcass characteristics of small and medium-fra me Aberdeen Angus young steers, finished in feedlot and slaughtered with similar subcutaneous fat th ickness are evaluated. The average age and live weight at the start of feedlot were respectively 298 days and 202 kg. The steers were confined during 158 days, and slaughtered with average subcutaneous fat thickness of 6.4 mm. The feed consisted of sorghum silage and concentrate at 60:40 ratio of dry matter duri ng the first 63 days and 50:50 afterward. The frame was calculated by formula F =-11.548 + (0.4878xh) - (0.0289xID) + (0.0000146xID²)+(0.0000759xIDxh), where h is the height and ID the age, in days. Steers with medium frame showed superiority in important marketing aspects such as warm (p < 0.0001) and cold carcass (p < 0.0001) weights. Muscularity measurements such as longissimus dorsi area in relation to cold carcass (p = 0.0477) an d empty body (p = 0.0419) weights were lower for medium-frame steers. Carcass conformation, longissimus dorsi area and cushion thickness were similar in both frame. The commercial cuts, forequarter (p < 0.001), flank (p = 0.009) and saw cut (p = 0.0003) in kg were higher for medium-frame steers. Saw cut decrea sed 0.18% with an increase in frame (p = 0.0404). Weight of the carcass tissues increased with the st eers frame, whereas the percentage of muscle tissue decreased 0.57% (p = 0.0410).